The Effect of First Aid Training on Accidents (PPPK) on Knowledge of Fracture Handling of the “Pagar Nusa” Pencak Silat Trainer in Semanding District - Suhartono Suhartono; Novia Dwi Astuti (Aloha International Journal of Health Advancement (AIJHA), 2020)
Martial arts sports (body contact) have a very high risk of injury. This is due to several causes of injury, including fractures in both the upper and lower extremities. The purpose of this study was to determine the effect of first aid training on accidents (P3K) on knowledge of fracture handling of the pencak silat trainer "Pagar Nusa" in Semanding District. This study uses Pre-Experimental Designs with the type of one-group pretest-posttest design. The population in this study were all trainers of pencak silat fence nusa in the district of semading as many as 32 respondents, with a sample size of 32 respondents who were determined using simple random sampling technique. The instruments used were SOPs and questionnaires which were then analyzed using the Wilcoxon test. Almost all respondents (76.7%) have sufficient knowledge of fracture management. Meanwhile, after being given treatment, most of the respondents (53.3%) had good knowledge of fracture handling. The results of the Wilcoxon test statistical test showed a p-value of 0.003 where p